2012
DOI: 10.1155/2012/124527
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Resistance Exercise and Parkinson's Disease: A Review of Potential Mechanisms

Abstract: This paper reviews the therapeutically beneficial effects of progressive resistance exercise (PRE) on Parkinson's disease (PD). First, this paper discusses the rationale for PRE in PD. Within the first section, the review discusses the central mechanisms that underlie bradykinesia and muscle weakness, highlights findings related to the central changes that accompany PRE in healthy individuals, and extends these findings to individuals with PD. It then illustrates the hypothesized positive effects of PRE on nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
1
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 100 publications
2
64
1
11
Order By: Relevance
“…This disorder leads to impairments in the recruitment of motor units, and contributes to bradykinesia and muscle weakness. RT has been proposed as an effective intervention aimed at reducing muscle weakness, bradykinesia and balance problems . Several studies have shown the efficacy of strength training in improving lower limb strength, gait and balance in PD patients…”
Section: Discussionmentioning
confidence: 99%
“…This disorder leads to impairments in the recruitment of motor units, and contributes to bradykinesia and muscle weakness. RT has been proposed as an effective intervention aimed at reducing muscle weakness, bradykinesia and balance problems . Several studies have shown the efficacy of strength training in improving lower limb strength, gait and balance in PD patients…”
Section: Discussionmentioning
confidence: 99%
“…19,125 Future research should more closely examine the effects of resistance training on non-motor symptoms in PD, especially cognition, which may relate to reduced levels of homocysteine and/or increased levels of insulin-like growth factor I. 206 At the same time, resistance training may facilitate motor improvements via increased neural drive and central neural changes, such as cross-education and reduced agonist-antagonist coactivation. 207 These mechanisms may be relevant for PD given the reduced muscle activation observed in the disorder, which largely contributes to bradykinesia and muscle weakness.…”
Section: Potential Mechanisms Of Action Of Exercise On Mood Cognitiomentioning
confidence: 99%
“…207 These mechanisms may be relevant for PD given the reduced muscle activation observed in the disorder, which largely contributes to bradykinesia and muscle weakness. 206 Drawing from functional neuroimaging studies, resistance training may also promote functional neuroplasticity in the cortex and basal ganglia, although all of these potential mechanisms require further study in PD. 206 For a review of potential mechanisms of resistance exercise in PD, please see 206 .…”
Section: Potential Mechanisms Of Action Of Exercise On Mood Cognitiomentioning
confidence: 99%
“…Dopaminergic loss in subjects with Parkinson's Disease (PD) results in reduction in corticospinal activaction with deficit in the recruitment of motor units, contributing to muscle weakness and bradykinesia 1 . Moreover, tissue changes such as the selective loss of type II muscle fibers in subjects with PD can contribute to the inability to generate strength during the performance of fast movements 2 .…”
Section: Introductionmentioning
confidence: 99%